On Fuzzy Groups and Group Homomorphism - Tawfiq, L. N. M.; Qa’aed, M. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this paper, we study the effect of group homomorphism on the chain of level subgroups of fuzzy groups. We prove a necessary and sufficient conditions under which the chains of level subgroups of homomorphic images of an a arbitrary fuzzy group can be obtained from that of the fuzzy groups . Also, we find the chains of level subgroups of homomorphic images and pre-images of arbitrary fuzzy groups